Time and belief in exercise importance predict increased activity during initial COVID-19 restrictions in Ireland - Barrett, Emer; Forde, Cuisle (My University, 2021)
The aim of this work was to investigate physical activity levels and the associated barriers and facilitators to physical activity in Irish adults during initial COVID-19 restrictions. Members of the general population completed an online questionnaire. Responses from 1274 participants (1274/1568, 81% completion rate) indicated that the majority (46.1%, n = 587) of people were more active than usual during the restrictions, however, 28.6% (n = 365) reported being less active. Fifty-five percent (55.3%, n = 702) of participants were meeting public health physical activity guidelines and more than half (53.3%, n = 679) reported finding new ways to be active. Walking (86%, n = 1101), physical activity in the home (47%, n = 593) and online resources (38%, n = 483) were the most frequently reported types of physical activity people engaged in. Having more time to be physically active [OR 2.326 (SD 1.948–2.794)] and a greater belief in the importance of physical activity [OR 1.192 (SD 1.001–1.444)] were predictive of exercising more than usual. Being unable to access their usual means of exercise [OR 1.612 (SD 1.369–1.902)], advised not to go outside the home [OR 1.402 (SD 1.165–1.698)] and working more than usual [OR 1.201 (SD 1.013–1.443)] were predictive of exercising less than usual. There was a positive trend in physical activity engagement by Irish adults during initial COVID-19 restrictions, likely influenced by increased time, belief that exercise was important and increased use of home-based and online exercise resources. However, almost one in three people reported being less active than usual, highlighting the need for targeted support during restriction periods.
PUBLISHED
Keywords: Physical activity; Exercise; COVID-19; Facilitators; Barriers; PHYSICAL ACTIVITY; Population Health; physical activity promotion; Chronic Health Condition; Health; Policy; Sports